Effects of a ciliary neurotrophic factor (CNTF) small-molecule peptide mimetic in an in vitro and in vivo model of CDKL5 deficiency disorder - Nicola Mottolese; Manuela Loi; Stefania Trazzi; Marianna Tassinari; Beatrice Uguagliati; Giulia Candini; Khalid Iqbal; Giorgio Medici; Elisabetta Ciani (Journal of Neurodevelopmental Disorders)
Abstract Background Mutations in the X-linked CDKL5 gene underlie a severe epileptic encephalopathy, CDKL5 deficiency disorder (CDD), characterized by gross motor impairment, autistic features and intellectual disability. Absence of Cdkl5 negatively impacts neuronal proliferation, survival, and maturation in in vitro and in vivo models, resulting in behavioral deficits in the Cdkl5 KO mouse. While there is no targeted therapy for CDD, several studies showed that treatments enabling an increase in brain BDNF levels give rise to structural and behavioral improvements in Cdkl5 KO mice. P021, a tetra-peptide derived from the biologically active region of the human ciliary neurotrophic factor (CNTF), was found to enhance neurogenesis and synaptic plasticity by promoting an increase in BDNF expression in preclinical models of brain disorders, such as Alzheimer’s disease and Down syndrome, resulting in a beneficial therapeutic effect. Considering the positive actions of P021 on brain development and cognition associated with increased BDNF expression, the present study aimed to evaluate the possible beneficial effect of treatment with P021 in an in vitro and in vivo model of CDD. Methods We used SH-CDKL5-KO cells as an in vitro model of CDD to test the efficacy of P021 on neuronal proliferation, survival, and maturation. In addition, both young and adult Cdkl5 KO mice were used to evaluate the in vivo effects of P021, on neuroanatomical and behavioral defects. Results We found that P021 treatment was effective in restoring neuronal proliferation, survival, and maturation deficits, as well as alterations in the GSK3β signaling pathway, features that characterize a human neuronal model of CDKL5 deficiency. Unexpectedly, chronic in vivo P021 treatment failed to increase BDNF levels and did not improve neuroanatomical defects in Cdkl5 KO mice, resulting in limited behavioral benefit. Conclusions At present, it remains to be understood whether initiating the treatment prenatally, or prolonging the duration of treatment will be necessary in order to achieve similar results in vivo in CDD mice to those obtained in vitro.